Multiblock residual-based compact schemes for the computation of complex turbomachinery flows. (1st January 2011) - Michel, B.; Cinnella, P.; Lerat, A.
A flexible multiblock implementation of second and third-order accurate residual-based compact (RBC) schemes is proposed and validated for turbomachinery flows of increasing complexity. Applications to complex transonic unsteady flows in turbomachinery show the advantages of using such schemes in terms of increased accuracy and better insight into the flow physics.